1979
DOI: 10.1111/j.1365-2125.1979.tb00989.x
|View full text |Cite
|
Sign up to set email alerts
|

Drugs and human memory: effects of low doses of nitrazepam and hyoscine on retention.

Abstract: 1 The effects of diazepam (5 mg) and hyoscine hydrobromide (0.3 mg) were assessed in two memory tasks: short-term retention of digit strings and the free recall of items from categorizable lists. 2 One hundred and two healthy subjects were tested in an independent-groups design. Subjects were assigned randomly to either placebo, diazepam or hyoscine groups. Treatments were administered orally under double-blind conditions. 3 The short-term, retention of digits was impaired to an equivalent degree and locus for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…However, they found that intravenous diazepam (0.1 1 mg/kg) and scopolamine (5.7 pg/kg) had essentially similar effects. They also replicated the Jones et al (1979) finding that scopolamine affected both early and middle parts of a sequence, while diazepam caused most impairment in the middle part only (Jones et al, 1978). A second study at the MRC Clinical Research Centre failed to show any difference in the effect of diazepam and scopolamine on different types of distractors or cues on homophone and synonym word-list learning .…”
Section: The Nature Of the Amnesiasupporting
confidence: 51%
“…However, they found that intravenous diazepam (0.1 1 mg/kg) and scopolamine (5.7 pg/kg) had essentially similar effects. They also replicated the Jones et al (1979) finding that scopolamine affected both early and middle parts of a sequence, while diazepam caused most impairment in the middle part only (Jones et al, 1978). A second study at the MRC Clinical Research Centre failed to show any difference in the effect of diazepam and scopolamine on different types of distractors or cues on homophone and synonym word-list learning .…”
Section: The Nature Of the Amnesiasupporting
confidence: 51%
“…While we know of no evidence relating drug effects to colour memory, we do accept that hyoscine does produce a fairly specific impairment in primary memory (e.g. Jones et al 1979;Preston et al 1988). It is not obvious what this might imply for colour memory, but to explain our data it would have to mean that impairment in colour memory increases the saturation of the remembered colour.…”
Section: Discussionmentioning
confidence: 93%
“…In normal human volunteers, it is well established that scopolamine, a muscarinic receptor antagonist, impairs the acquisition of new information and disrupts the process of memory consolidation (Drachman and Leavitt 1974;Petersen 1977;Jones et al 1979;Broks et al 1988) as well as impairing continuous performance in a task that challenges sustained attentional mechanisms (Colquhoun 1962;Wesnes andWarburton 1983, 1984;Broks et al 1988). These findings clearly implicate the cholinergic system in both attentional and memory processes, but the precise relationship between these two functions is far from resolved.…”
mentioning
confidence: 99%